OPTIMIZATION, FORMULATION AND CHARACTERIZATION OF NANO BASED TDDS OF EPLERENONE - VITHOBA, SHINDE RAMESH; VELRAJ, MALARKODI (International Journal of Applied Pharmaceutics, 2023)
Objective: The proposed work was aimed to formulation, characterization and optimization of transdermal patches of nanoparticles of eplerenone for efficient transdermal delivery of the drug. Methods: Eplerenone nanoparticles transdermal patches were formulated by the casting evaporation method. Transdermal patches were made using combinations of hydroxypropyl methylcellulose (HPMC), Eudragit RS 100. Physical characterization evaluation (organoleptic properties, pH, weight uniformity, thickness uniformity, percent moisture content, and tensile strength) was then performed. The permeation of eplerenone nanoparticles into the skin was evaluated using Franz diffusion cell. Results: Eplerenone nanoparticles transdermal patches could be formulated by the casting evaporation method with the thickness of the patches ranged from 0.10±0.11 mm to 0.15±0.54 mm. The average weight of the patches 4 cm2 patches ranged from 350±0.202 mg to 386±0.527 mg, and the percent moisture content ranged from 1.0 to 6.0%. Folding endurance of prepared patches was in the range of 355±0.20 to 368±0.20. Prepared batches NS1 to NS9 evaluated for percentage moisture uptake and loss as well as for pH measurement. The result of in vitro drug release study for batch NS9 containing 30 %/cm 2/h and 87.74 % released in 16 h. Conclusion: All patches met the requirement of the physical characterization for the transdermal patch.